A Preliminary Note on Compression Loss in Plywood - Gupta, R. C.; Shah, R. S. (Indian Forester, 1983)
It is natural that plywood gets compressed under certain pressing conditions, but the data regarding Indian species of wood is not available. The present note evaluates tbe Compression loss in plywood made from Mangifera indica and Terminalia myriocarpa for a few pressing conditions and thickness of plywood. This knowledge may be useful to the industry to evalnate the final thickness of plywood produced by tbem from veneers.